CHILDREN’S LITERATURE ON THE CONTEMPORARY WAR: INTERPRETING CHILDREN’S EXPERIENCES THROUGH STORIES (BASED ON MATERIALS FROM THE COLLECTION "APY "UKRAINE" AND OTHER TALES FROM THE WAR" BY DARA KORNII) - Kapustian, Inha; Martynets, Alla (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
This article examines the children’s dimension of the works of the contemporary Ukrainian author Dara Kornii. The aim of the study is to analyse the specificity of the artistic representation of war in texts addressed to children, focusing on the collection “Apiary ‘Ukraine’ and Other Fairy Tales of War.” The research methodology combines elements of cultural-historical and intellectual-historical approaches. The analysis of the texts is further informed by contemporary theoretical frameworks, particularly trauma studies and cultural memory studies. The results demonstrate that, in Kornii’s works for children, war is represented not only as a historical event but also as an experience of the loss of security, the disruption of the familiar world, and the necessity of adaptation. In addition, the study explores the indirect modes of representing traumatic experience through fairy-tale poetics, symbolism, and allegory. The scientific novelty of the article lies in demonstrating that children’s literature performs not only an aesthetic function but also therapeutic and social functions, contributing to the formation of historical memory and moral orientation in young readers. The practical significance of the study consists in the possibility of applying its results in courses on contemporary Ukrainian children’s literature.